2009
DOI: 10.1007/s00198-009-0891-4
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk in patients receiving acid-suppressant medication alone and in combination with bisphosphonates

Abstract: ASM is associated with an increased risk of fracture when taken alone or in combination with bisphosphonates. Given the frequency of coprescription of ASM and bisphosphonates, this issue requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 25 publications
6
83
1
Order By: Relevance
“…Multiple observational studies have shown PPIs do indeed increase the risk of fractures, particularly hip fractures compared to non-users of PPIs. The reported HRs for increased risk of any fractures are typically quite modest, ranging from 1.15 to 1.43 [28,29]. Additionally, the increase risk for hip fractures associated with PPI use was also quite modest (RR 1.30, 95 % CI 1.19-1.43) based on a meta-analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple observational studies have shown PPIs do indeed increase the risk of fractures, particularly hip fractures compared to non-users of PPIs. The reported HRs for increased risk of any fractures are typically quite modest, ranging from 1.15 to 1.43 [28,29]. Additionally, the increase risk for hip fractures associated with PPI use was also quite modest (RR 1.30, 95 % CI 1.19-1.43) based on a meta-analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The authors' study results clearly indicate that antacid medications in BP users would be expected to reduce gastric irritable symptoms, because the serum level of pepsinogen is correlated to gastric acidity. However, several recent reports [23][24][25] indicate that antacid treatments including PPI and H2RA increased the risk of hip fractures among patients undergoing BP treatment. The exact mechanism behind the reason why patients treated with PPI have higher susceptibility to fractures even under BP treatment is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the risk of hip fracture was markedly increased among long-term users of high-dose PPI therapy. PPIs were recently identifi ed as an independent risk factor for osteoporotic fracture (14,(27)(28)(29)(30)(31). PPIs reportedly increase the risk of osteoporotic fracture by causing hypochlorhydria, reducing intestinal calcium absorption and subsequently inducing a negative calcium balance (26,30).…”
Section: Discussionmentioning
confidence: 99%